Evaluation of the Key Performance Indicators of the In Vitro Fertilization (IVF) Program at the Permata Hati Clinic, Dr. Sardjito in 2019-2020 - Bayu Rizky Prabowo; Shofwal Widad; Addin Trirahmanto (JURNAL KESEHATAN REPRODUKSI, 2022)
Evaluation of the Key Performance Indicators of the In Vitro Fertilization (IVF) Program at the Permata Hati Clinic, Dr. Sardjito in 2019-2020Bayu Rizky Prabowo, Shofwal Widad, Addin TrirahmantoObstetric dan Gynecology DepartmentFaculty of Medicine, Public Health, and Nursing Gadjah Mada UniversityDr. Sardjito Central General Hospital YogyakartaABSTRACTBACKGROUND: One of the efforts that can be done to overcome infertility is In Vitro Fertilization (IVF) or the IVF process is a process in which the egg is fertilized by sperm outside the body. Where in the In Vitro Fertilization effort, hormone stimulation is carried out, in principle, is an effort to add a number of hormones from the outside (exogenous hormone) which functions as control of the reproductive process, so that the reproductive cycle can be accelerated or can be carried out outside its natural environment. Given the many risks that arise, a measurement is needed to determine the success rate of the IVF program itself. Research Performance indicator or key performance indicator (KPI) is a type of performance measurement of any process, whether in biomedical or non-biomedical fields, may be subject to inherent deviations from the optimum limit or from the set limit.METHODS: This research is a descriptive observation because the researcher only observes without treating the object to be studied. This research was conducted at Dr. RSUP. Sardjito because RSUP Dr. Sardjito owns the Permata Hati infertility clinic, which provides patients with IVF (in vitro fertilization or IVF) procedures. Data collection was carried out especially in the medical record section which was carried out in January 2019 - January 2020.RESULTS: The variables of ICSI damage level, normal ICSI fertilization rate, normal IVF success rate, IVF fertilization failure rate, blastocyst cryosurvival rate, and implantation level (cleavage stage) have not been able to meet the key performance indicators. , and the implantation rate (blastocyst stage) met the key performance indicatorsCONCLUSION: Permata Hati Clinic Performance RSUP Dr. Sardjito is still under competency and aspirational performance based on key performance indicators.KEYWORDS Key Performace Indicator, In Vitro Fertilization, Assisted reproductive technique